KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Weiss, Emiliana [UNESP] (2021)
KIR2DL4 is an important immune modulator expressed in natural killer cells; HLA-G is its main ligand. We have characterized the KIR2DL4 genetic diversity by considering the promoter, all exons, and all introns in a highly admixed Brazilian population sample and by using massively parallel sequencing. We introduce a molecular method to amplify and to sequence the complete KIR2DL4 gene. To avoid the mapping bias and genotype errors commonly observed in gene families, we have developed and validated a bioinformatic pipeline designed to minimize these errors and applied it to survey the variability of 220 individuals from the State of São Paulo, southeastern Brazil. We have also compared the KIR2DL4 genetic diversity in the Brazilian cohort with the diversity previously reported by the 1000Genomes consortium. KIR2DL4 presents high linkage disequilibrium throughout the gene, with coding sequences associated with specific promoters. There are few but divergent promoter haplotypes. We have also detected many new KIR2DL4 sequences, all bearing nucleotide exchanges in introns and encoding previously described proteins. Exons 3 and 4, which encode the external domains, are the most variable. The ancestry background influences the KIR2DL4 allele frequencies and must be considered for association studies regarding KIR2DL4.